Intensive Soybean Management : an Integrated Systems Approach - Balboa, Guillermo R. (2017)
Ecological intensification impacted soybean yield, biomass and N uptake. Narrow row spacing, high seeding rate, other best production practices, and balanced nutrition increased partitioning effi ciency for biomass, measured by seed harvest index (HI), grain N, and N HI (NHI). Partial factor productivity of fertilizer (PFPf) increased when best production and fertilizer management practices were implemented in combination, with 19% and 28% increases under irrigated and dryland scenarios, respectively. An integrated approach, simultaneously considering multiple management factors in a farming system, is needed for closing exploitable yield gaps